2015
DOI: 10.3346/jkms.2015.30.4.398
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Predictive Clinicopathologic Factors for Lymph Node Metastasis in Patients with Early Colorectal Carcinoma

Abstract: The objective of this study was to conduct a meta-analysis to determine risk factors that may facilitate patient selection for radical resections or additional resections after a polypectomy. Eligible articles were identified by searches of PUBMED, Cochrane Library and Korean Medical Database using the terms (early colorectal carcinoma [ECC], lymph node metastasis [LNM], colectomy, endoscopic resection). Thirteen cohort studies of 7,066 ECC patients who only underwent radical surgery have been analysed. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 35 publications
6
73
2
2
Order By: Relevance
“…Kitajima et al reported that the rate of LNM was 0% if the depth was < 1000 µm . Another review showed the depth of ≥ 1000 µm was a risk factor of LNM . In this study, however, the invasion depth turned out not to be significant, because five lesions developed LNM among 61 cases with < 1000 µm.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Kitajima et al reported that the rate of LNM was 0% if the depth was < 1000 µm . Another review showed the depth of ≥ 1000 µm was a risk factor of LNM . In this study, however, the invasion depth turned out not to be significant, because five lesions developed LNM among 61 cases with < 1000 µm.…”
Section: Discussioncontrasting
confidence: 59%
“…31 Another review showed the depth of ≥ 1000 μm was a risk factor of LNM. 32 In this study, however, the invasion depth turned out not to be significant, because five lesions developed LNM among 61 cases with < 1000 μm. It does not mean that this result lacks in consistency with, for example, the following cases.…”
Section: Discussioncontrasting
confidence: 57%
“…Other studies also reported higher rates of LNM in female compared with male patients, although these differences were not statistically significant (11,12). Several systematic reviews and meta-analyses have investigated risk factors for LNM; however, none has focused on patient gender as a predictive factor for LNM to date (13)(14)(15)(16)(17). The aim of the present systematic review and meta-analysis was to assess whether the gender of patients with T1 colorectal cancer is predictive of LNM.…”
Section: Introductionmentioning
confidence: 80%
“…As LNM is difficult to assess preoperatively, the decision to perform radical surgery following endoscopic resection is based on the results of clinicopathological analysis. Several previous systematic reviews of small, retrospective studies have identified reliable pathological factors associated with the risk of LNM in T1 colorectal cancer (13)(14)(15)(16)(17). These meta-analyses reported that depth of submucosal invasion >1,000 µm, lymphovascular invasion, poorly differentiated tumors and tumor budding were all risk factors for LNM.…”
Section: Discussionmentioning
confidence: 99%
“…Aiding the accurate histopathologic diagnosis of specimens is one of the primary reasons for recommending ESD in guidelines from both Japan and Europe, and the types of lesion where this is particularly recommended will be discussed in further detail below 20,35,37. In addition, en bloc resection allows curative endoscopic resection of adenocarcinoma with early submucosal invasion, as lymph node metastases are rare in adenocarcinoma with only superficial submucosal invasion or invading <1000 µm from the muscularis mucosae 38,39. In fact, several series have demonstrated that, in the absence of high-risk histopathologic factors including lymphovascular invasion, poor differentiation or tumor budding, early colorectal cancer with only superficial submucosal invasion or invasion to a depth of <1000 µm is associated with a risk of lymph node metastases approaching 0% 4046.…”
Section: Introductionmentioning
confidence: 99%